Taking University to the Students : Forging Connections and Inclusion Through Regional University Centres (RUCs). - Stone, Cathy; King, Sharron; Ronan, Chris (Student Success v.13 n.3 p.46-53 https://doi.org/10.5204/ssj.2434, 2022)
For regional students, going to university frequently involves moving away from important home, family and community connections to forge new connections in unfamiliar environments. This is a daunting prospect discouraging many from considering university as an option. But what if university could come to them, allowing them to stay where they feel most connected, whilst also becoming connected with other students and developing a sense of inclusion within university culture? Recent research with high school students in regional South Australia indicates that the combination of online delivery (increasingly mainstreamed due to COVID-19) and the growing presence of Regional University Centres (RUCs) may provide the opportunity for this to happen. This paper discusses these findings within the context of the challenges for regional students in moving away from their connections. It argues that, instead, important learning connections may be offered within their local communities through the collaboration between universities and RUCs. [Author abstract]